Multi-instrumental detection of a fireball during Leonids of 2019 - Szárnya, Cs.; Chum, J.; Podolská, K.; Kouba, D.; Koucká Knížová, P.; Mošna, Z.; Barta, V. (Frontiers in Astronomy and Space Sciences, 2023)
During the 2019 Leonid meteor shower, the European Fireball Network recorded a bright fireball (meteor code: EN171119_041459) at 04:15:0.2 (UT) on 17 November 2019. The fireball appeared at coordinates 49.95° N 15.56° E at the height of 134.46 km, and disappeared at coordinates 50.23° N 15.26° E and at the height of 71.81 km. The ionization effect caused by the fireball appeared in the digisonde’s campaign measurements taken with a 2 ionogram/min time resolution at Průhonice station (50.00° N, 14.60° E). The trace appeared on the ionograms as a faint sporadic E-like layer, and the maximum ionization reached the upper limit of the measurement, 17 MHz. The trace persisted for 20 minutes on the ionograms, first appearing at 04:15:40 (UT) and finally disappearing at 04:35:40 (UT). The virtual height of the trace according to the ionograms appeared between 114 and 142 km, first it descended and then it ascended. Drift measurements were also taken with the digisonde every minute. Between 04:19:20 and 04:35:20 (UT), between altitudes of 122-142 km, 1-5 reflections were recorded on most SkyMaps. In addition, the Continuous Doppler Sounding developed by the Institute of Atmospheric Physics of Prague also recorded the ionization signature of the fireball between 04:18 and 04:30 (UT) on 2 of the 3 sounding paths operating at 4.65 MHz. This is the first evidence that the plasma trail of a documented fireball can be detected by a DPS-4D digisonde (not only on ionograms, but also by drift measurements) and by the Continuous Doppler Sounding system.